9x-18=-36

Simple and best practice solution for 9x-18=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-18=-36 equation:


Simplifying
9x + -18 = -36

Reorder the terms:
-18 + 9x = -36

Solving
-18 + 9x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 9x = -36 + 18

Combine like terms: -18 + 18 = 0
0 + 9x = -36 + 18
9x = -36 + 18

Combine like terms: -36 + 18 = -18
9x = -18

Divide each side by '9'.
x = -2

Simplifying
x = -2

See similar equations:

| 9x+1=9x-7 | | (80-x)3x=180 | | 4x-1=8-2x | | 8+3q=11+2q | | -13=6-7 | | 2x-2=6x-4 | | 2x-4(x-3)=-9+5x-14 | | 3b+12-5b=22 | | 0.07-0.06(5x+4)=0.06x+0.13 | | 4x+13=-7x-30 | | 4x^2-26-14= | | 32m+54m+22=0 | | 6x-4x+20=-16 | | 2+3v=-6v-16 | | 3x+20+2(4x+4)=2x | | 26-(4x-11)=5(x+7) | | -(5z+1)=18 | | 4x+8-3x=14 | | 6x^3=5x^2 | | 3x+5.2=2-5y | | x+5=x+0 | | -13+7=-h-7+7 | | 3x-15=17-x | | 3(5y+2)-y=(2y-3) | | x=23-(-11) | | 8-3x=3x+2 | | 66=9x-13-8x+29 | | x/8+6=-12 | | 23-(-11)= | | w+(-9)=-4 | | 3x-15=3x | | 8x=6x-14 |

Equations solver categories